What role in the nitrogen supply do organic fertilizers have for organic farming? - Aschan, Arvid (SLU/Dept. of Economics, 2017)
The demand for organic products has been substantially increasing, which has been noted by Lantmännen, one of Northern Europe´s largest agricultural cooperative. With the increasing demand for organic products, Lantmännen has set a goal of doubling its trade in organic grain by year 2020. The increased demand for organic products is also noticeable on the supply side; Swedish organic arable land has almost doubled during the last decade. In addition to its trade in organic grain, Lantmännen also markets organic-approved products to increase the yield of organic grains; and increased yields is perceived to be an important aspect in realizing the mission for 2020. One of the most important product Lantmännen offers for increasing organic grain yield is Biofer, an organic fertilizer from Gyllebo Gödning. The trade of Biofer has, despite the increased demand for organic products, been relatively stable during the same period. The aim in this study is to find out why the trade of Biofer does not correspond to the increased use of land for organic farming. To find the answer, the researcher has completed an empirical study based on interviews with organic farmers to learn about their decision making concerning the use of purchased fertilizers on their farms. It was found from the empirical study that the economy of the individual farmer was the most determining factor, which also affects all buy phases in the famers’ decision-making process. However, there were some economic factors of the buying decision process that neither the farmers nor the researcher could verify. Those factors included: current competition, product substitutes and cereal prices. After analysing the three factors the researcher concludes that cereal prices don´t have any connection to traded volumes of Biofer. Consequently, the product substitute manure and the competitor Ekoväx are the two factors that are perceived to affect the buying decision. Biofer is an added source of nutrients and is not included in the organic cycle in the same way as organic manure and therefore entails a higher cost. These are the reasons why it´s hard for Biofer to increase on the market and compete with manure in organic fertilizing. The competitor Ekoväx affects the farmers´ buying decision since the company competes for the same market shares and consequently, the same customers- the organic farmers.